2017
DOI: 10.1016/j.scienta.2017.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Refrigerated storage and calcium dips of ripe ‘Celeste’ sweet cherry fruit: Combined effects on cell wall metabolism

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.0 de Creative Commons Elsevier Editorial System(tm) for Scientia Horticulturae Manuscript Draft

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 40 publications
0
23
0
3
Order By: Relevance
“…The AM activity was determined by the method of Bonghi, Pagni, Vidrih, Ramina, and Tonutti (1996). The absorbance was measured at 540 nm and the result was expressed as U/g.…”
Section: Starch Content and Am Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The AM activity was determined by the method of Bonghi, Pagni, Vidrih, Ramina, and Tonutti (1996). The absorbance was measured at 540 nm and the result was expressed as U/g.…”
Section: Starch Content and Am Activitymentioning
confidence: 99%
“…The carboxylic groups of de‐esterified pectins are cross‐linked by Ca 2+ in middle lamella of cell wall, which helps to strengthen the cell‐wall structure (Demarty, Morvan, & Thellier, 1984; Thor, 2019). To date, several studies have conducted to study the effects of postharvest calcium treatment on storage quality, softening and cell wall degradation during fruit ripening (Belge, Goulao, Comabella, Graell, & Lara, 2017; Gao, Xiong, Li, Chen, & Zhu, 2019; Liu et al., 2017; Martins, Garcia, Costa, Sottomayor, & Gerós, 2018). However, the influence of calcium on softening of red raspberry fruit stored at low temperature has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Ngamchuachit et al [10] found that fresh-cut Tommy Atkin mangos treated with 0.136 M CaCl 2 at 10°C for 2.5 min maintained better texture and other qualities than control. Belge et al [11] found that cherry fruit with 3% CaCl 2 treatment for 2 min showed lower water loss and slower delay than the control. Some advances had recently focused on the combination of HT and CaCl 2 treatment in postharvest fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent watering or exogenous applications of boron, calcium and/or growth promoters, such as GA 3 , can reduce cracking. Applications of calcium and boron strengthen the linkages between polysaccharides in the cell wall, increasing firmness 19,20 . Applications of GA 3 likely decrease cracking because this treatment increases the deposition of cuticular material in the epidermis and makes it more elastic 21,22 .…”
Section: Introductionmentioning
confidence: 99%